The Crux at Hebrews 5,7-8 - Swetnam, James (Biblica, 2000)
Heb 5,7-8 is a classic crux. It is not clear, as the text seems to say, how Jesus could beg to be freed from death and then be heard `although He was son'. Further, it is not clear how Jesus could `learn obedience from the things He suffered' since Hebrews pictures Him as antecedently ready to do God's will. The present paper reviews some of the principal suggestions which have been made and makes its own: that the Sitz im Leben of Jesus' plea is the cross, and the words refer to Ps 22 which Jesus cites in Matthew and Mark. In the context, reference to the psalm is taken by bystanders as an allusion to God intervening through Elijah to save Jesus. Hebrews understands Jesus' citing the initial verse of the psalm as an agreement to all that the psalm implies, i.e., as an implicit petition to die. Further, the main verse alluded to in Ps 22 seems to refer to the tôdâ which Jesus celebrated with His disciples, and this explains how He could `learn' obedience: He learned by experience the benignant effect of obedience to God.